An audit of change in clinical practice: from oxygen‐driven to air‐driven nebulisers for prehospital patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Issue 6 (12th June 2018) - Heys, Deborah; Swain, Andrew; Knowles, Sarah; Waugh, Amy; Bailey, Mark
Abstract: Background: In developed countries, ambulances normally carry oxygen cylinders, but not compressed air. Treatment of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) with oxygen‐driven nebulisers can result in hypercapnia and acidosis. Attempts to avoid this have involved interrupted administration of oxygen. However, small battery‐powered air nebulisers are now available. This study aims to compare the prehospital oxygen saturations and treatment of patients suffering from AECOPD before and after the introduction of air nebulisers. Methods: The oxygen saturations and treatment of 200 AECOPD patients before and 200 AECOPD patients after the introduction of air nebulisers were compared. Compliance with a target saturation of 88–92% was calculated. Results: The median final oxygen saturation was lower for the post‐intervention category (94%) than the pre‐intervention category (96%). There was an increase in air nebuliser use from 0 to 56% ( P < 0.001) and a decrease in oxygen use from 100 to 71.5% ( P < 0.001). There was a numerical increase in the proportion of patients arriving at hospital with oxygen saturations of 88–92% following introduction of the air nebulisers (24 vs 16.5%) and a decrease in patients arriving with high saturations (67.5 vs 76.5%). The likelihood of achieving the target oxygen saturations following introduction of air nebulisers increased (odds ratio 1.598; 95% confidence interval 0.974, 2.621). Conclusion: The introduction of prehospital air nebulisers resulted in a reduction in oxygen therapy in patients with AECOPD and a lower median prehospital oxygen saturation. This study supports the use of air nebulisers in the prehospital setting.